2010
DOI: 10.1103/physreva.81.023631
|View full text |Cite
|
Sign up to set email alerts
|

Fast production of ultracold sodium gases using light-induced desorption and optical trapping

Abstract: In this article we report on the production of a Bose-Einstein condensate (BEC) of 23 Na using light-induced desorption as an atomic source. We load about 2 × 10 7 atoms in a magneto-optical trap (MOT) from this source with a ∼6 s loading time constant. The MOT lifetime can be kept around 27 s by turning off the desorbing light after loading. We show that the pressure drops down by a factor of 40 in less than 100 ms after the extinction of the desorbing light, restoring the low background pressure for evaporat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…It is immediate to generalize them to any trapping potentials and boundary conditions. They open a way to solve the long-standing problem of the BEC and other phase transitions [1][2][3][4][5][6][7][8][9][10][11][12], including a restricted canonical ensemble problem [2], and describe numerous modern laboratory and numerical experiments on the critical phenomena in BEC of the mesoscopic systems [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is immediate to generalize them to any trapping potentials and boundary conditions. They open a way to solve the long-standing problem of the BEC and other phase transitions [1][2][3][4][5][6][7][8][9][10][11][12], including a restricted canonical ensemble problem [2], and describe numerous modern laboratory and numerical experiments on the critical phenomena in BEC of the mesoscopic systems [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…It becomes possible due to the newly developed methods of (a) the nonpolynomial averages and contraction superoperators [15,16], (b) the partial difference (recurrence) equations [17][18][19] (a discrete analog of the partial differential equations) for superoperators, and (c) a characteristic function and cumulant analysis for a joint distribution of the noncommutative observables. They allow us to take into account (I) the constraints in a many-body Hilbert space, which are the integrals of motion prescribed by a broken symmetry in virtue of a Noether's theorem, and constraintcutoff mechanism, responsible for the very existence of a phase transition and its nonanalytical features, [4,20,21] (II) an insufficiency of a grand-canonical-ensemble approximation, which is incorrect in the critical region [2,8] because of averaging over the systems with different numbers of particles, both below and above the critical point, i.e., over the condensed and noncondensed systems at the same time, that implies an error on the order of 100% for any critical function, (III) a necessity to solve the problem for a finite system with a mesoscopic (i.e., large, but finite) number of particles N in order to calculate correctly an anomalously large contribution of the lowest energy levels to the critical fluctuations and to avoid the infrared divergences of the standard thermodynamic-limit approach [5][6][7][8][9][10][11] as well as to resolve a fine structure of the λ-point, (IV) a fact that in the critical region the Dyson-type closed equations do not exist for true Green's functions, but do exist for the partial 1-and 2-contraction superoperators, which reproduce themselves under a contraction.The problem of the critical region and mesoscopic effects is directly related to numerous modern experiments and numerical studies on the BEC of a trapped gas (including BEC on a chip), where N ∼ 10 2 − 10 7 , (see, for example, [22][23][24][25][26][27][28][29][30][31][32][33]) and superfluidit...…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has attracted particular attention in laser cooling and trapping experiments using ultrahigh vacuum cells, into which atoms can be loaded quickly on demand from the surface by LIAD techniques [13,14]. However, most LIAD studies [13,[15][16][17][18][19] focused only on desorbed atoms, and lack of basic knowledge of the surface itself leads to a poor understanding of desorption mechanisms and also some contradictory practical information. For example, one group reported that LIAD from quartz glass is not effective [20], but another loaded a magneto-optical trap in a quartz cell by LIAD [16].…”
mentioning
confidence: 99%
“…Therefore, either the organic compound is optimized for minimum contamination of the residual background pressure, or the light-desorption effect is obtained from other surfaces, including the glass or metallic walls of the vacuum chamber or thin metal layers [56,65,[67][68][69][70].…”
Section: Liad From Organic Coatings For Cold Atomsmentioning
confidence: 99%